A Fast and Efficient Single-stranded Genomic Library Preparation Method Optimized for Ancient DNA. (25th March 2021) - Kapp, Joshua D; Green, Richard E; Shapiro, Beth
Abstract: We present a protocol to prepare extracted DNA for sequencing on the Illumina sequencing platform that has been optimized for ancient and degraded DNA. Our approach, the Santa Cruz Reaction or SCR, uses directional splinted ligation of Illumina's P5 and P7 adapters to convert natively single-stranded DNA and heat denatured double-stranded DNA into sequencing libraries in a single enzymatic reaction. To demonstrate its efficacy in converting degraded DNA molecules, we prepare 5 ancient DNA extracts into sequencing libraries using the SCR and 2 of the most commonly used approaches for preparing degraded DNA for sequencing: BEST, which targets and converts double-stranded DNA, and ssDNA2.0, which targets and converts single-stranded DNA. We then compare the efficiency with which each approach recovers unique molecules, or library complexity, given a standard amount of DNA input. We find that the SCR consistently outperforms the BEST protocol in recovering unique molecules and, despite its relative simplicity to perform and low cost per library, has similar performance to ssDNA2.0 across a wide range of DNA inputs. The SCR is a cost- and time-efficient approach that minimizes the loss of unique molecules and makes accessible a taxonomically, geographically, and a temporally broader sample of preserved remains for genomic analysis.